Аналіз структури та умов спікання алмазно-металевих композицій з урахуванням оптимального поєднання компонентів в алмазоносному шарі шліфувальних кругів - Сушко, Ольга Вікторівна; Сушко, Ольга Викторовна; Sushko, Olha (ТДАТУ, 2019)
UK: В статті наведений аналіз структури та умов спікання алмазно-металевих композицій з урахуванням оптималного поєднання компонентів в алмазоносному шарі спечених шліфувальних кругів. Показано, що найважливішим фактором, що забезпечує працездатність алмазних шліфувальних кругів, є цілісність зерен, що їх складають. Доведено, що в експлуатацію потрапляють шліфувальні круги з характеристиками, які суттєво відрізняються від наведених в маркуванні. Тобто, такі круги не можуть реалізовувати очікувані показники алмазної абразивної обробки. З метою визначення умов, які забезпечують мінімальне руйнування алмазних зерен в процесі спікання кругів, досліджений процес виготовлення алмазних шліфувальних кругів на металевій зв’язці методом порошкової металургії. Визначені основні характеристики алмазоносного шару, які визначають його експлуатаційні властивості: марка алмазу, зернистість алмазного порошку, концентрація, марка зв’язки, її фізико-механічні та хімічні властивості. Розглянуті особливості етапів отримання інструменту: брикетування, спікання та гарячої допресовки з урахуванням оптимального вибору температури, що дозволяє знизити вихідну дефектність алмазних зерен та підвищити міцність та зносостійкість металевої композиції в цілому. RU: В статье приведен анализ структуры и условий спекания алмазно-металлических композиций с учетом оптимального сочетания компонентов в алмазоносных слое спеченных шлифовальных кругов. Отмечено, что важнейшим фактором, обеспечивающим работоспособность алмазных шлифовальных кругов, является целостность входящих в них зерен. Показано, что в эксплуатацию попадают шлифовальные круги с характеристиками, которые существенно отличаются от приведенных в маркировке. То есть, такие круги не могут реализовывать ожидаемые показатели алмазной абразивной обработки. С целью определения условий, обеспечивающих минимальное разрушение алмазных зерен в процессе спекания кругов, исследован процесс изготовления алмазных шлифовальных кругов на металлической связке методом порошковой металлургии. Определены основные характеристики алмазоносного слоя, определяющие его эксплуатационные свойства: марка алмаза, зернистость алмазного порошка, концентрация, марка связки, ее физико-механические и химические свойства. Рассмотрены особенности этапов получения инструмента: брикетирования, спекания и горячей допрессовки с учетом оптимального выбора температуры, что позволяет снизить исходную дефектность алмазных зерен и повысить прочность и износостойкость металлической композиции в целом. EN: The use of synthetic superhard materials (SHM) in various sectors of the economy is a determining factor for improving existing and creating new tools and instrumental materials, as well as technological processes, reducing production costs, improving their quality, and increasing the service life of machine parts and tools. However, there remains the problem of increasing the processing efficiency of these materials. Diamond grinding as a traditional SHM machining process is expensive and low-productive, often characterized by the unstable quality of the products being machined. Existing brands of binder and diamond grinding powders used in diamond wheels differ significantly in their strength properties. The recommendations in the literature for the use of diamonds and metallic bonds are quite general and have very wide ranges. Such recommendations, given the high cost of diamond grains (which can vary hundreds of times depending on the brand of grain), lead to low efficiency of their use and high cost of the diamond grinding process, which significantly impedes its use in the processing process. The article analyzes the structure and conditions of sintering of diamond-metal compositions, taking into account the optimal combination of components in the diamond layer of sintered grinding wheels. It is shown that the most important factor in ensuring the performance of diamond grinding wheels is the integrity of the grains that make them. It is proved that grinding wheels with characteristics that differ significantly from those given in the marking come into operation. That is, such circles cannot meet the expected performance of diamond abrasive machining. To determine the conditions that ensure the minimum destruction of diamond grains during sintering of the wheels, we studied the process of manufacturing diamond grinding wheels on a metal binder by powder metallurgy. The basic characteristics of the diamond-bearing layer are determined, which determine its performance properties: diamond brand, grain of diamond powder, concentration, bond brand, its physics-mechanical and chemical properties. The features of the stages of obtaining the tool are considered: briquetting, sintering and hot pressing, taking into account the optimal temperature choice, which allows reducing the initial defect of diamond grains, increase the strength and durability of the metal composition as a whole.
Анализ структуры и условий спекания алмазно-металлических композиций с учетом оптимального сочетания компонентов в алмазоносном слое шлифовальных кругов
Analysis of the structure and sintering conditions of diamond-metal compositions, taking into account the optimal combination of components in diamond-cutting layers of grinding wheels
Keywords: синтетичні надтверді матеріали; абразивний інструмент; шліфувальні круги; алмазні зерна; шліфувальні порошки; металева зв’язка; алмазно-металеві композиції; синтетические сверхтвердые материалы; абразивный инструмент; шлифовальные круги; алмазные зерна; шлифовальные порошки; металлическая связка; алмазно-металлические композиции; are synthetic superhard materials; abrasive tools; grinding wheels; diamond grains; grinding powders; metal bonding; diamond metal compositions